Developing trauma resilient communities through community capacity-building - Todd P. Gilmer; Kimberly Center; Danielle Casteel; Kyle Choi; Debbie Innes-Gomberg; Amy E. Lansing (BMC, 2021)
Abstract Background Trauma is a significant public health issue, negatively impacting a range of health outcomes. Providers and administrators in public mental health systems recognize the widespread experience of trauma, as well as their limited ability to address trauma within their communities. In response, the Los Angeles County Department of Mental Health funded nine regionally based community partnerships to build capacity to address trauma. We describe partnership and community capacity-building efforts and examine community impact, defined as successful linkages to resources and changes in stress tolerance capacities among community members. Methods We conceptualized community capacity-building as dissemination of trauma-informed education and training, community outreach and engagement, and linkage of community members to resources. We measured trauma-informed trainings among partnership members (N = 332) using the Trauma-Informed Organizational Toolkit. Outreach, engagement and linkages were documented using Event and Linkage Trackers. We examined changes in the type of successful linkage after the issuance of statewide mandatory restrictions in response to COVID-19. We examined changes in stress tolerance capacities among community members (N = 699) who were engaged in ongoing partnership activities using the 10-item Conner-Davidson Resilience Scale; the 28-item Coping Orientation to Problems; and the pictorial Inclusion of Community in Self Scale. Results Training and education opportunities were widespread: 66% of members reported opportunities for training in 13 or more trauma-informed practices. Partnerships conducted over 7800 community capacity-building events with over 250,000 attendees. Nearly 14,000 successful linkages were made for a wide range of resources, with consistent linkage success prior to (85%) and during (87%) the pandemic. In response to COVID-19, linkage type significantly shifted from basic services and health care to food distribution (p < .01). Small but significant improvements occurred in coping through emotional and instrumental support; and sense of community connectedness (p < .05 each). Conclusions Community-based partnerships demonstrated effective capacity-building strategies. Despite the pandemic, community members did not report reduced stress tolerance, instead demonstrating gains in external help-seeking (use of emotional and instrumental supports) and perception of community connectedness. Future work will use qualitative methods to examine the impact of community capacity-building and the sustainability of this approach for addressing the impact of trauma within communities.